Designing with hidden data - Stephanie Posavec (Oz, 2010)
Many aspects of our world can be explained by mathematics and so, thus, can be broken down into series of numbers. The patterns found in numbers are often hidden to the viewer, as most examples of these patterns cannot be seen with the naked eye.